Achievement motivation and e-learning engagement among physical education students: A correlational study in Algeria - Kenioua Mouloud; Ben Daken Ahmed (spdfharmony.com, 2026)
Background: Achievement motivation plays a crucial role in shaping students’ engagement and effectiveness in e-learning environments, particularly in higher education settings focused on physical and sports sciences. Aims: This study investigated the relationship between achievement motivation and e-learning among students at the Institute of Physical and Sports Activities Sciences and Technologies at Kasdi Merbah University, Ouargla, Algeria. Methods: A correlational, descriptive approach was adopted using a random sample of 35 students from the soccer and volleyball specializations. A questionnaire including an achievement motivation scale (23 items) and an e-learning scale (27 items) was used. Result: Results revealed high levels of achievement motivation (M = 3.41, SD = 0.70) and e-learning (M = 3.45, SD = 0.76) among participants. The study found a very strong, statistically significant positive correlation (r = 0.90, p < 0.05) between the two variables, with a coefficient of determination of 0.81, indicating that 81% of the variance in e-learning can be explained by achievement motivation. Conclusion: The study recommends enhancing motivational strategies in e-learning environments, improving technological infrastructure, and supporting students' self-regulated learning.